2020
DOI: 10.1108/jabs-03-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality and employee loyalty: an empirical investigation among millennials in India

Abstract: Purpose The purpose of this paper examines the relationship between dimensions of workplace spirituality (meaningful work, sense of community and alignment with organizational values) and employee loyalty (intention to stay, benefit insensitivity toward alternate employers and word of mouth about the organization), in the context of millennials who are three times more likely to change jobs, than other generations. Design/methodology/approach This descriptive study was conducted among a sample of 308 employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
(80 reference statements)
2
36
1
1
Order By: Relevance
“…Over the last decade, researchers in management have developed more interest in identifying the significance and function of spirituality in the workplace. Several research studies have proposed various definitions by putting workplace spirituality in a larger framework, both from the business and an individual perspective (Saxena et al, 2020;Aboobaker et al, 2020). Workplace spirituality is about having a spiritual structure and a corporate culture reflected in the shape of the spiritual self, compassion, and care, sense of belonging, acceptance, honesty, kindness, and wholeness (Aboobaker et al, 2019).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…Over the last decade, researchers in management have developed more interest in identifying the significance and function of spirituality in the workplace. Several research studies have proposed various definitions by putting workplace spirituality in a larger framework, both from the business and an individual perspective (Saxena et al, 2020;Aboobaker et al, 2020). Workplace spirituality is about having a spiritual structure and a corporate culture reflected in the shape of the spiritual self, compassion, and care, sense of belonging, acceptance, honesty, kindness, and wholeness (Aboobaker et al, 2019).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…Some of the researchers who focus on the first choice often had inconsistent findings; some even found no relationship between religiosity and job stress. For example, Aboobaker et al (2019) found a positive correlation between workplace spirituality and employee loyalty. Similarly, Kalhori et al (2018) found that students’ spiritual well-being affected their PsyCap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nayak et al (2018) recommended that linking workplace empowerment to the quality of work life will help employees to withstand work situations and challenges and stay motivated. Aboobaker et al (2020) surveyed 308 millennial employees working in different private sectors in India and concluded that workplace’s spirituality is positively related to all the dimensions of the employee’s loyalty toward its organization.…”
Section: Six Sigma Critical Success Factors: a Literature Reviewmentioning
confidence: 99%